Sub-daily zenith total delay time series for GPS stations on bedrock for Antarctica and the sub Antarctic sector, 1995-2021 - Eric Buchta; Mirko Scheinert; Matt King; Terry Wilson; Peter J Clarke; Demián Gómez; Eric Kendrick; Christoph Knöfel; Achraf Koulali (PANGAEA, 2025)
The GIANT-REGAIN (Geodynamics In ANTarctica based on REprocessing GNSS dAta Initiative) project aimed to reprocess and provide consistent GPS time series of all available GPS stations on bedrock in Antarctica from 1995 to 2021. Four analysis centres processed the GPS data and, in addition to daily station coordinates, estimated tropospheric signal delays in the form of zenith total delays (ZTD). Here we provide the resulting time series of ZTD for each station and from each analysis centre. The TUD, OSU and UTAS analysis centres provide time series with a temporal resolution of one hour, while the NEWC solutions have a resolution of two hours. The dataset consists of tab-delimited text files, with each file named using the following convention <station_id>_GR2023_ztd_<ac>.tab. The <station_id> is a unique identifier for the GPS station within this dataset consisting of the four character site code and the IERS domes code (if assigned to the station), <GR2023> refers to the GIANT-REGAIN project, <ztd> denotes the zenith total delay, and <ac> indicates the analysis centre (newc, osu, tud, utas).
In: Buchta, E et al. (2025): Daily coordinate time series for GPS stations on bedrock for Antarctica and the sub Antarctic sector, 1995-2021, reprocessed by the GIANT-REGAIN project [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.967515